Development of highly performing TiO2 complex thin films by novel combined physico-chemical process for enhanced photo-catalytic applications. Issue 8 (1st June 2020) - Karthick, P.; Thanmathikalai, T.; Manoj Cristopher, M.; Saravanakumar, K.; Gopalakrishnan, C.; Jeyadheepan, K.
Abstract: Structural, morphological, optical, photoresponse and photo-catalytic properties of TiO2 nanostructured thin films, prepared through novel combined physico-chemical (GLADOX) process by varying the electrolyte ratio have been investigated. TiO2 nanoporous structured thin films were prepared by anodization of Ti thin films, prepared on FTO substrate by using DC magnetron sputtering equipped with the glancing angle arrangement and by varying electrolyte ratio of anodization. The structural studies show that the TiO2 nanostructured thin films have a crystal structure of tetragonal with a crystalline phase of rutile with an appreciable secondary phase; monoclinic TiO. The morphological studies reveal the nanoporous structure of the GLADOX deposited TiO2 thin films. The optical studies show that the absorbance and band gap of the optimized TiO2 thin films prepared at optimized electrolyte ratio are ideal for photo-catalytic applications. The photo-catalytic properties of TiO2 nanostructured thin films were investigated by the degradation of methylene blue (MB) dye in the presence of visible light and the influence of secondary phase on the photo-catalytic performance is also investigated with the support of photoresponse studies.